PENGARUH KESEHATAN BANK TERHADAP TINGKAT INKLUSI KEUANGAN PADA BANK BNI KOTA GUNUNGSITOLI HENCE ANYCOLONY HUMENDRU - Humendru, Hence Anycolony; Harefa, Idarni; Bate’, Maria M; Bu’ulolo, Nanny (Jurnal Suluh Pendidikan, 2024)
The aim of this research is to examine the effect of bank health on the level of financial inclusion. This research uses sample collection techniques by distributing questionnaires. The research sample is customers of PT. Bank Negara Indonesia, Gunungsitoli city, was screened based on certain criteria or a purposive sampling technique, totaling 100 respondents. SMART-PLS is used as an analytical tool to test research hypotheses. The research results obtained were that there was a positive and significant influence on the research entitled "The Influence of Bank Health on the Level of Financial Inclusion at Bank BNI in the city of Gunungsitoli". Based on the results of data analysis and discussion, it can be concluded that health has a significant positive effect on financial inclusion. From the results of the hypothesis test, it is known that the P-Values ​​that form the influence of Bank Health on Financial Inclusion is 0.000, which means the variable has an influence. Then look at the value of 10,882. This is of course in accordance with the standard T-Statistics value of >1.96, which means it is significant.